Astragalus Polysaccharides/Chitosan Microspheres for Nasal Delivery: Preparation, Optimization, Characterization, and Pharmacodynamics - Wang, Saisai; Sun, Yuqing; Zhang, Jingjing; Cui, Xiaoming; Xu, Zhilu; Ding, Dejun; Zhao, Limin; Li, Wentong; Zhang, Weifen (Frontiers in Pharmacology, 2020)
Chitosan (CTS) constitutes a promising area in treatment of nose-related diseases as a nasal drug delivery carrier. Astragalus polysaccharide (APS) significantly attenuates eosinophils and neutrophil-dominant airway inflammation, and it has a potential pharmaceutical application in the treatment of severe asthma. The purpose of this work was to prepare APS/CTS microspheres intended for nasal drug delivery by the spray-drying method. The characteristics of APS/CTS microspheres were evaluated by a scanning electron microscope, Fourier transform infrared spectroscopy, differential scanning calorimetry, and in vitro drug release. The effect of APS/CTS microspheres on rats with allergic rhinitis (AR) was investigated by eosinophil and neutrophil counts in nasal lavage fluid. Results of SEM showed that microspheres were spherical and wrinkled. In vitro release showed that 67.48–93.76% APS was released from APS/CTS microspheres at pH 6.8 within 24 h. The effects showed that APS/CTS microspheres alleviated allergic symptoms and reduced eosinophils infiltration and the expression of interleukin-4 in the nasal mucosa tissue of rats that had no liver and kidney toxicity by hematoxylin-eosin staining observation. In conclusion, these results indicated that APS/CTS microspheres had excellent characteristics for the treatment of AR.